Evaluación del control interno en la Importadora Jorua Cia. Ltda. - Fernández Fuentes, Karla Michael (2021)
The internal control within the company, carries a transcendental importance, because within this process it allows them to protect all the resources that the company has in order to avoid fraud, negligence or losses, as well as to be able to detect effectively any deviations that are present. The evaluation of internal control within the company, allows tests of the effectiveness of its systems, be they accounting or administrative. Within the evaluation of internal control, the management of its five components is executed, these help us to comply with all the policies and procedures that must be carried out to obtain the goals proposed by their superiors.